2018
DOI: 10.1002/adsc.201800615
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Tandem Reaction of Quinazolinone‐Based Nitriles with Arylboronic Acids: Synthesis of 2‐(4‐Arylquinazolin‐2‐yl)anilines

Abstract: A palladium-catalyzed tandem reaction of 2-(quinazolinone-3(4H)-yl)benzonitriles with arylboronic acids has been developed, allowing access to a new class of 2-(4-arylquinazolin-2-yl)anilines that were often difficult to prepare using previous methods. In particular, the newly produced amino group is amenable to further synthetic elaborations, thereby broadening the diversity of the products. The structure of the newly synthesized 2-(4-arylquinazolin-2-yl)anilines was unambiguously confirmed by X-ray crystallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Many 3,4-dihydroquinazolin-2(1 H )-one derivatives have been previously synthesized (Huang et al, 2008; Khan et al, 2014, 2015, 2016; Kshirsagar, 2015; Camacho et al, 2016; Maiden and Harrity, 2016; Awad et al, 2018; Zhang et al, 2018; Elkholy et al, 2019; Gatadi et al, 2019; Long et al, 2019; Wang et al, 2019). For example, Wang et al (2009) reported the synthesis of 4-alkyl-2(1H)-quinazolinones via the cyclization of 1-(2-alkynyl-phenyl)ureas catalyzed by TfOH and Saunthwal et al (2015) described a green and catalyst-free straightforward tandem synthesis of functionalized tetrahydroquinazolines from 2-aminophenylacrylate.…”
Section: Introductionmentioning
confidence: 99%
“…Many 3,4-dihydroquinazolin-2(1 H )-one derivatives have been previously synthesized (Huang et al, 2008; Khan et al, 2014, 2015, 2016; Kshirsagar, 2015; Camacho et al, 2016; Maiden and Harrity, 2016; Awad et al, 2018; Zhang et al, 2018; Elkholy et al, 2019; Gatadi et al, 2019; Long et al, 2019; Wang et al, 2019). For example, Wang et al (2009) reported the synthesis of 4-alkyl-2(1H)-quinazolinones via the cyclization of 1-(2-alkynyl-phenyl)ureas catalyzed by TfOH and Saunthwal et al (2015) described a green and catalyst-free straightforward tandem synthesis of functionalized tetrahydroquinazolines from 2-aminophenylacrylate.…”
Section: Introductionmentioning
confidence: 99%
“…A similar combination of reactions has been extended to the synthesis of quinazolines by using quinazolinone-based aryl nitriles as the substrates (Scheme 28). 39 In this reaction, the mechanism is almost the same as that of their previous synthetic approach for the synthesis of isoquinolines, 37 except for the ring-opening by a nucleophile and subsequent hydrolytic quenching of the imine moiety to obtain the desired quinazolines with an aniline substituent (Scheme 29).…”
Section: Scheme 27 Proposed Mechanism For the Pd-catalyzed Formation mentioning
confidence: 88%
“…Later, the same research group disclosed another methodology for quinazoline scaffolds 65 from reaction of aryl boronic acids 61 with 2-(quinazolinone-3(4 H )-yl)benzonitriles 64 . This tandem synthesis involved nucleophilic addition, followed by intramolecular cyclization and subsequent ring-opening, delivering the corresponding product in moderate to excellent isolated yields (31–93%) ( Scheme 21C ) (Zhang et al, 2018 ). In another interesting report by Chen et al, the synthesis of 2,4-disubstituted quinazoline derivatives 66 through Pd–catalyzed reaction of aryl boronic acids 61 with N -(2-cyanoaryl)benzamides 60 by employing 1,10-phen, trifluoroacetic acid in THF at 80°C has been described ( Scheme 21D ).…”
Section: Transition Metal-catalyzed Methodologiesmentioning
confidence: 99%